2016
DOI: 10.1177/1687814016683600
|View full text |Cite
|
Sign up to set email alerts
|

Public-participant quick cable force investigation method using smartphone for bridges in disaster area

Abstract: Numerous infrastructures, especially the bridge, require some safe inspection and assessment at the soonest when hit by a disaster like catastrophic earthquake. However, plenty of bridges within disaster area and limited resources for inspections may lead to the traffic delays and hampering the quick post-disaster assessment and rebuilt. In this article, a public-acceptant method, where cable force of bridges can be investigated quickly based on ubiquitous smartphones, was proposed to raise the efficiency of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…With this validation study, they have shown that tension cable force can be inferred from a smartphone providing a low-cost alternative to traditional and expensive instrumentation and eventually expanded the validation protocol to an actual cable-stayed bridge study. The same researchers also presented a framework for the cloud operation nature of smartphones for cable vibration monitoring with an app called Orion-CC [ 49 ] and discussed the potential of using it in a public participation framework [ 50 ]. They performed similar observations with a broader range of experimental and field studies, where many cables were monitored with smartphone sensors and the frequency–cable force relationships were compared using a reference system [ 51 ].…”
Section: Invasive Smartphone Sensing For Bridge Monitoringmentioning
confidence: 99%
“…With this validation study, they have shown that tension cable force can be inferred from a smartphone providing a low-cost alternative to traditional and expensive instrumentation and eventually expanded the validation protocol to an actual cable-stayed bridge study. The same researchers also presented a framework for the cloud operation nature of smartphones for cable vibration monitoring with an app called Orion-CC [ 49 ] and discussed the potential of using it in a public participation framework [ 50 ]. They performed similar observations with a broader range of experimental and field studies, where many cables were monitored with smartphone sensors and the frequency–cable force relationships were compared using a reference system [ 51 ].…”
Section: Invasive Smartphone Sensing For Bridge Monitoringmentioning
confidence: 99%